2016
DOI: 10.1302/0301-620x.98b1.36293
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of failure in total knee arthroplasty

Abstract: Total knee arthroplasty (TKA) is a cost effective and extremely successful operation. As longevity increases, the demand for primary TKA will continue to rise. The success and survivorship of TKAs are dependent on the demographics of the patient, surgical technique and implant-related factors. Currently the risk of failure of a TKA requiring revision surgery ten years post-operatively is 5%. The most common indications for revision include aseptic loosening (29.8%), infection (14.8%), and pain (9.5%). Revision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
177
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(196 citation statements)
references
References 49 publications
(59 reference statements)
5
177
0
14
Order By: Relevance
“…A similar observation was recently reported in a major review study conducted by Khan et al. (2016), where a shift from infection to aseptic loosening occurred 2.5 years after the primary TKA operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar observation was recently reported in a major review study conducted by Khan et al. (2016), where a shift from infection to aseptic loosening occurred 2.5 years after the primary TKA operation.…”
Section: Discussionmentioning
confidence: 99%
“…The confounders were chosen based on clinical experience and the previous literature (Khan et al. 2016). All covariates fulfilled the assumption of proportional hazards when tested by Schoenfeld residual test.…”
Section: Methodsmentioning
confidence: 99%
“…The decreasing trend of revisions due to wear debris clearly indicates that improvements in PE manufacturing, sterilization, and design were key to increasing the device survival [49]. However, this study demonstrates that PE debris in and of itself may not be responsible for the loss of cement-bone interlock in functioning TKAs.…”
Section: Discussionmentioning
confidence: 95%
“…However, this study demonstrates that PE debris in and of itself may not be responsible for the loss of cement-bone interlock in functioning TKAs. Considering the rates of revision are now at ~5% for 10 years post implantation for some devices [49], looking beyond PE debris to other potential causes of aseptic loosening may be necessary to further improve the longevity of TKA. Note that all of implants in this study were unrevised, clinically successful implants at time of death.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relative frequency of this operation, recent research shows over a fifth of patients are left dissatisfied with their post-surgical outcomes [5] and this figure is higher in younger patient age groups. Younger patients undergoing primary TKR are also far more likely to require revision surgery in the future due to increased demands and expectations following surgery [6]. Furthermore, a recent analysis performed by Ferket et al found that current practice on TKR operations leads to minimal changes in quality of life and quality adjusted life years, and is only cost-effective in older patients with severe symptoms [7].…”
Section: Introductionmentioning
confidence: 99%